KEEFEKTIFAN PEMBELAJARAN IPA MATERI PESAWAT SEDERHANA MENGGUNAKAN MODEL PAIR CHECK BERBANTU QUESTION CARD PADA SISWA KELAS V SDN SUKOHARJO 01 PATI - Oktaviana, Bela; Saputra, Henry Januar; Arifin, Zaenal (Profesi Pendidikan Dasar, 2018)
AbstractThe purpose of this study was to determine the effectiveness of science learning in simple aircraft material using Pair Check assisted learning questions. Question Card for fifth grade students of SDN Sukoharjo 01 Pati. This research is quantitative. The research method using one group pretest-posttest design. Based on the results of the analysis data obtained the initial test or pre-test conducted by researchers obtained data on average class 60.59259 there were 25 students did not complete KKM 75 with students who completed only 2 students. Then the class was given treatment, namely Natural Science learning about Simple Aircraft material using the Pair Check assisted Question Card model. Learning outcomes obtained by students after the treatment of post-test scores showed that class V obtained an average of 78.81481 with students completing 22 and who had not completed 5 students. In the final analysis of calculations using t test is obtained if Î± = 0.05 and db = N-1 = 27-1 = 26 obtained t table = 2.056 and thitung = 14.578. If thitung t table, then Ho is rejected and Ha is accepted, so Pair Check is assisted with an effective Question Card towards the learning outcomes of class V students of SDN Sukoharjo 01 Pati.Â